Graphene Nanoribbons @ Vanadium Oxide Nanostrips for Supercapacitive Energy Storage. (10th March 2017) - Sahu, Vikrant; Goel, Shubhra; Kumar Tomar, Anuj; Singh, Gurmeet; Sharma, Raj Kishore
Graphical abstract: Highlights: ∼15 wt% GNR in VOS@GNRnanocompositeplaysacrucialroleinminimizationtheiR-drop. (*). VOS@GNR shows high capacitance 335.8 F g −1 at 1 A g −1 . High cycling stability with ∼98.5% capacitance retention & high workable current density. V2 O5 over GNR, improved conductivity and ionic accessibility leading to low iR-drop. Abstract: Nanocomposite GNR@VOS composed of V2 O5 nanostrips (VOS) embedded over graphene nanoribbons (GNR) is synthesized by facile hydrothermal route and examined as supercapacitor electrode. GNR as support in mere ∼15 wt% plays an important role in patterning the nanocomposite growth as a template. Selective formation of VOS leads to ordered growth and at the same time channelizes the microstructural (shape/size, porosity) as well electrochemical characteristics of the nanocomposite. GNR@VOS so formed is highly accessible electrode matrix in which the underlying GNR acts as conducting support to efficiently minimize the internal resistance (iR-drop) of the electrode. The study suggests that the conductive properties of VOS can be enhanced by integration with GNR displaying increased solid-state conductivity by two orders (bare VOS: 4.2 × 10 −4 S m −1 and GNR@VOS: 1.4 × 10 −2 S m −1 ). These attributes result in high energy density for GNR@VOS as 42.09 Wh kg −1 at power density 475 W kg −1 . The enhanced performance of GNR@VOS supercapacitor cell from low (1 A g −1 ) to high current density (20 A g −1 ) is attributed to the balanced ionic and electronic conduction.